Efficacy, Safety and Mechanism of Jinzhen Oral Liquid in the Treatment of Acute Bronchitis in Children: A Randomized, Double-Blind, Multicenter Clinical Trial Protocol - Cui, Xin; Liang, Long; Geng, Hongjiao; Liu, Yi; Xi, Junyu; Wang, Junhong; Ching, Tee Bee; Bee, Eow Gaik; Chai, Yan; Wu, ShengXian; Jin, De; Xie, YanMing (Frontiers in Pharmacology, 2022)
Background: Acute bronchitis (AB) is a common disease in pediatrics. Prolonged AB may develop into chronic bronchitis. Bronchitis caused by the influenza virus can lead to severe hypoxia or insufficient ventilation, causing great harm to patients and increasing the burden on children and society. Presently, there is no specific treatment for AB except symptomatic supportive treatment. It is urgent to find an effective treatment for AB. Jinzhen Oral Liquid (JZOL) has been found to have a broad spectrum of anti-inflammatory and antiviral effects in previous clinical and basic studies and has a good effect on AB in children. However, the large-sample, randomized, double-blind, head-to-head, evidence-based studies are lacking. The purpose of this study is to evaluate the efficacy, safety, and mechanism of JZOL in the treatment of AB in children. Methods: This is a randomized, double-blind, parallel-controlled multi-center clinical trial. The sample size is 500 participants in the intervention group and the control group respectively, with a total of 1000 participants. The Intervention group takes JZOL and Ambroxol Hydrochloride and Clenbuterol Hydrochloride Oral Solution (AHCHOS) placebo, while the control group receives AHCHOS and JZOL placebo. The dosage of the two drugs varies according to age and weight. The medication lasts for seven days. The disappearance time of cough is adopted as the primary outcome. SAS is used for statistical analysis. All statistical tests are conducted using a two-sided test, and P≤0.05 would be considered statistically significant. Discussion: We hypothesized that children with AB could get good health benefits from JZOL. This study not only evaluates the clinical efficacy and safety of JZOL but also conducts metagenomics analysis and metabolomics analysis of feces and saliva of participants to study the mechanism of JZOL against AB. Therefore, this study evaluates the efficacy, safety, and mechanism of JZOL from a comprehensive perspective, so as to obtain a more solid evidence chain, which will enhance the credibility of the evidence. If successful, this study will provide a high-level evidence-based reference for the treatment of AB in children and future relevant studies.